Fostering sustainability by management education - Stachowicz-Stanusch, Agata; Amann, Wolfgang (Contemporary perspectives in corporate social performance and policy (Series), 2018)
This book presents our set of insights and solutions for more effectively integrating corporate social responsibility into management education. Internationally acclaimed authors critically review this multifaceted process in a variety of countries. The book is divided into several sections. After the introduction, three parts delve deep on the following aspects: "Values, Ethics and Spirituality in Management Education", "Embedding CSR in Management Education", and "University Social Responsibility". This book combines theoretical considerations and state-of-the-art, practical advice. The purpose of this book is to ensure graduates pay enough attention to CSR, become more interested in it, trigger a desire for action and feel well equipped to implement tailored initiatives. Future business leaders and managers ought to become change agents who can more easily cope with the complexities CSR entails.